2005
DOI: 10.1159/000088700
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation in the Dentate Gyrus of Rat Hippocampus Is Inhibited by Soft Diet Feeding

Abstract: Background: Recently it has become well accepted that neurogenesis occurs in the dentate gyrus of the hippocampus, a region important to memory and learning function in rodents and humans. Reports show that neurogenesis in the hippocampus is regulated by certain factors, such as exposure to an enriched environment, physical activity, aging and stress. The relationship between the change in the task of chewing as one oral environmental factor, and the mechanisms of hippocampal neuron generation are unclear. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…Interestingly, food texture also has an impact on AHN; rats fed with a soft diet, as opposed to a solid/hard diet, exhibit decreased hippocampal progenitor cell proliferation. The authors hypothesize that chewing resulting in cell proliferation is related to corticosterone levels [4]. Interestingly, independent studies have shown impairment in learning and memory abilities with similar soft diets [59,114].…”
Section: Dietary Modulation Of Adult Hippocampal Neurogenesismentioning
confidence: 99%
“…Interestingly, food texture also has an impact on AHN; rats fed with a soft diet, as opposed to a solid/hard diet, exhibit decreased hippocampal progenitor cell proliferation. The authors hypothesize that chewing resulting in cell proliferation is related to corticosterone levels [4]. Interestingly, independent studies have shown impairment in learning and memory abilities with similar soft diets [59,114].…”
Section: Dietary Modulation Of Adult Hippocampal Neurogenesismentioning
confidence: 99%
“…Animal Model Intervention Outcome [10] Wistar rats Soft diet Cell proliferation in the dentate gyrus is suppressed by soft diet feeding [19] C57BL/6 mice Soft diet Soft diet mice showed behavioural impairments, such as decreased home cage activity, increased open field test activity, and deficits in prepulse inhibition, but no impairments in memory and learning. Decreased cell proliferation in the hippocampus, BDNF and Akt1 (protein kinase B) gene expression [36] C57BL/6 mice Hard diet Improved spatial learning ability of hard diet mice.…”
Section: Referencementioning
confidence: 99%
“…Experimental studies discussed, mainly done on mice, have consistently shown that impairing masticatory function results in both cellular and behavioural changes. A recurring theme identified is that of a decrease in neural stem cells proliferation in the hippocampus in many of the animal studies, when masticatory impairment was simulated by feeding mice a soft/powdered/liquid diet [10,19,33,34].…”
Section: Outcome Of Rodent Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Aoki et al 21 reported that feeding a soft diet inhibited cell proliferation in the dentate gyrus of the rat hippocampus. Kimoto et al 22 conducted a morphological study in rats and proved that tooth loss caused not only receptor loss but also neuro-nal death in the mesencephalic nucleus of the trigeminal nerve.…”
Section: Changes In Body Weightmentioning
confidence: 99%